Sistem Pakar Mendiagnosa Jenis Penyakit Stroke Dirumah Sakit Mulya Tangerang Mengunakan Metode Certainty Factor (CF - Septiansyah, Irfan; Herdiansyah, Rengga (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Stroke is a brain attack that arises suddenly where there is partial or complete disruption of brain function as a result of disruption of blood flow due to blockage or rupture of certain blood vessels in the brain, causing brain cells to lack blood, oxygen or nutrients and Eventually the death of these cells can occur in a relatively short time. The lifestyle in question is a change in diet from consuming traditional home-cooked meals to consuming junk food or fast food that is fast paced, rich in fat, and delicious. As well as changes in lifestyle that used to be relaxed and calm to become rushed, not having breakfast or even lunch, not having time to socialize and exercise. The method used is the Certainty Factor (CF) method or the certainty value of a disease. The purpose of this research is to create an expert system software that is expected to help the public in diagnosing the type of stroke. The development of this expert system software includes analysis of software requirements which consists of analysis of user requirements, analysis of system requirements and knowledge engineering design where in the manufacture of this software engineering the data collected is represented as a knowledge base, decisions, rule base and inference engine design. Furthermore, system design, which designs the creation of process modeling consisting of context diagrams and Data Flow Diagrams (DFD), data modeling consisting of Entity Relationship Diagram (ERD) designs, Mapping Tables and table designs. The next process development is implementation using Sublime Text 0.3 and the final stage of system development is testing with the Black box Test. The results of the research are in the form of an expert system application program that is able to diagnose as many as 3 Stroke Diseases. The system output is in the form of a disease diagnosis complete with MB values, MD values and CF values obtained by calculations using the Certainty Factor method, causes and solutions.